Evaluations of abusive supervisors: The moderating role of the abuser's gender. (12th November 2021) - Kim, Joseph K.; Harold, Crystal M.; Holtz, Brian C.
Summary: The present research examines the role of leaders' gender in influencing how employees evaluate abusive supervision. This paper argues that abusive supervision is considered to be a less typical leader behavior for female leaders, compared to male leaders, because abusive behaviors violate the stereotypes traditionally prescribed to female leaders (e.g., communal and caring). As such, drawing from gender stereotype theories (e.g., the lack‐of‐fit model and role congruity theory), we propose that, among leaders who engage in abusive supervision, employees will rate female leaders as less effective than male leaders. However, we also propose that employees will attribute female leaders' abuse to internal characteristics to a lesser extent than male leaders. Results from both an experimental study (Study 1) and a field study (Study 2) conducted with working adults support our hypotheses. Namely, results suggest that female leaders' abusive supervision is viewed as less typical leadership behavior and, consequently, is associated with lower ratings of effectiveness compared to abusive male leaders. Conversely, because abuse is viewed as female‐atypical behavior, employees were less likely to make internal attributions for female leaders' abusive behaviors. Implications for theory and practice will be discussed.